Peran Orang Tua Dan Komunitas Dalam Membangun Pendidikan Yang Inklusif - Inayatul Maula; Nur Khasanah (Yayasan Al-Afif, 2025)
Inclusive education requires collaborative efforts that extend beyond the classroom, making the role of parents and communities essential in ensuring every child’s right to learn without discrimination. This article examines how parental involvement and community participation contribute to creating learning environments that respect diversity and support students with different backgrounds, abilities, and social needs. Parents play a crucial role in reinforcing inclusive values at home, communicating openly with teachers, and advocating for their children's educational needs. Meanwhile, communities strengthen inclusion by providing social support, accessible resources, and positive cultural attitudes that encourage acceptance. The partnership between schools, families, and local communities builds a supportive ecosystem that enhances student engagement, emotional well-being, and equal opportunities. By understanding these interconnected roles, inclusive education becomes not only a school-based initiative but a shared social responsibility that promotes fairness and strengthens social cohesion.